Increased carbon monoxide in exhaled air of patients with cystic fibrosis. Issue 10 (1st October 1999) - Paredi, P; Shah, P L; Montuschi, P; Sullivan, P; Hodson, M E; Kharitonov, S A; Barnes, P J
Abstract : BACKGROUND: Inflammation, oxidative stress, and recurrent pulmonary infections are major aggravating factors in cystic fibrosis. Nitric oxide (NO), a marker of inflammation, is not increased, however, probably because it is metabolised to peroxynitrite. Exhaled carbon monoxide (CO), a product of heme degradation by heme oxygenase 1 (HO-1) which is induced by inflammatory cytokines and oxidants, was therefore tested as a non-invasive marker of airway inflammation and oxidative stress. METHODS: Exhaled CO and NO concentrations were measured in 29 patients (15 men) with cystic fibrosis of mean (SD) age 25 (1) years, forced expiratory volume in one second (FEV1 ) 43 (6)%, 14 of whom were receiving steroid treatment. RESULTS: The concentration of exhaled CO was higher in patients with cystic fibrosis (6.7 (0.6) ppm) than in 15 healthy subjects (eight men) aged 31 (3) years (2.4 (0.4) ppm, mean difference 4.3 (95% CI 2.3 to 6.1), p<0.001). Patients not receiving steroid treatment had higher CO levels (8.4 (1.0) ppm) than treated patients (5.1 (0.5) ppm, mean difference 3.3 (95% CI –5.7 to -0.9), p<0.01). Normal subjects had higher NO levels (6.8 (0.4) ppb) than patients with cystic fibrosis (3.2 (0.2) ppb, mean difference 3.8 (95% CI 2.6 to 4.9), p<0.05) and were not influenced by steroid treatment (3.8 (0.4) ppb and 2.7 (0.3) ppb for treated and untreated patients, respectively, mean difference 0.8 (95% CI –0.6 to 2.3), p>0.05). Patients homozygous for the ΔF508 CFTR mutation had higher CO and NO concentrations than heterozygous patients (CO: 7.7 (1.8) ppm and 4.0 (0.6) ppm, respectively, mean difference 3.7 (95% CI –7.1 to –0.3), p<0.05; NO: 4.1 (0.5) ppb and 1.9 (0.7) ppb, respectively, mean difference 2.2 (95% CI –3.7 to –0.6), p<0.05). CONCLUSIONS: High exhaled CO concentrations in patients with cystic fibrosis may reflect induction of HO-1. Measurement of exhaled CO concentrations may be clinically useful in the management and monitoring of oxidation and inflammatory mediated lung injury.